Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.22358/jafs/66968/2005
|View full text |Cite
|
Sign up to set email alerts
|

Effect of energy and protein supplementation on phosphorus utilization in lactating dairy cows

Abstract: Two experiments were undertaken in which grass silage was used in conjunction with a series of different concentrate types designed to examine the effect of carbohydrate source, protein level and degradability on total dietary phosphorus (P) utilization with emphasis on P pollution. Twelve Holstein-Friesian dairy cows in early to mid-lactation were used in an incomplete changeover design with four periods consisting of 4 weeks each. Phosphorus intake ranged from 54 to 80 g/day and faecal P represented the prin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…This database subset comprised data from lactating dairy cows from 25 studies (Martz et al, 1990;Morse et al, 1992;Spiekers et al, 1993;Delaquis and Block, 1995;Khorasani et al, 1997;Knowlton et al, 2001Wu et al, 2001Wu et al, , 2003Knowlton and Herbein, 2002;Guyton et al, 2003;Kebreab et al, 2005;Kincaid et al, 2005;Shore et al, 2005;Wu, 2005;Ekelund et al, 2006;Kamiya et al, 2006a;Knowlton et al, 2007;Dann et al, 2008;Moreira et al, 2009;Myers and Beede, 2009;Taylor et al, 2009;Van Straalen et al, 2009;Herrera et al, 2010;Puggaard et al, 2011) and included 130 treatment means. The response variable of interest was P excretion in the feces, both in grams per day and as a fraction of P intake.…”
Section: Databasementioning
confidence: 99%
See 3 more Smart Citations
“…This database subset comprised data from lactating dairy cows from 25 studies (Martz et al, 1990;Morse et al, 1992;Spiekers et al, 1993;Delaquis and Block, 1995;Khorasani et al, 1997;Knowlton et al, 2001Wu et al, 2001Wu et al, , 2003Knowlton and Herbein, 2002;Guyton et al, 2003;Kebreab et al, 2005;Kincaid et al, 2005;Shore et al, 2005;Wu, 2005;Ekelund et al, 2006;Kamiya et al, 2006a;Knowlton et al, 2007;Dann et al, 2008;Moreira et al, 2009;Myers and Beede, 2009;Taylor et al, 2009;Van Straalen et al, 2009;Herrera et al, 2010;Puggaard et al, 2011) and included 130 treatment means. The response variable of interest was P excretion in the feces, both in grams per day and as a fraction of P intake.…”
Section: Databasementioning
confidence: 99%
“…High dietary NDF levels also likely coincide with low levels of dietary starch and, in general, may be associated with a lower availability of fermentable substrate for microbes in the rumen, thus reducing P uptake by the ruminal microbes. Kebreab et al (2005) showed that type and density of energy in the feed have a significant effect on P excretion in cattle. In comparing 2 experiments with high and low energy intakes, they found that P efficiency improved significantly in cows fed a higher energy diet (consuming at least an extra 30 MJ/d).…”
Section: Fecal P (G/d)mentioning
confidence: 99%
See 2 more Smart Citations
“…Energy status of the animal Kebreab et al (2005a) conducted two experiments in which grass silage was used in conjunction with a series of different concentrate types designed to examine the effect of carbohydrate source, protein level and degradability on total dietary P utilization with emphasis on P pollution. The authors reported that dairy cattle excreted up to 15% less P when fed slow degradable starch sources compared with feed with high degradable starch content (Figure 1).…”
Section: Management Practices To Reduce Phosphorus Excretionmentioning
confidence: 99%